Exploratory study of dual‐task digital device in children and adolescents with attention‐deficit/hyperactivity disorder - Katsunaka Mikami; Tasuku Miyajima; Ryo Nishino; Naohiro Kawazoe; Toshimitsu Ochiai; Takashi Okada; Hiroki Fukuju (PCN Reports, 2025)
Abstract Aim The study aimed to assess the efficacy and safety of SDT‐001, a digital therapeutic, in Japanese children and adolescents with attention‐deficit/hyperactivity disorder (ADHD). Methods This phase 2, multicenter, randomized, double‐blind, sham‐controlled study (jRCT1080225158) was conducted for a duration of up to 14 weeks. After screening, eligible participants were randomized to receive SDT‐001 or single‐task intervention for 25 min/day for 6 weeks and followed for 4 weeks after the intervention. A post hoc analysis was also performed to compare the effects of SDT‐001 or a single‐task to a nonrandomized, open‐labeled, observational group (as the reference follow‐up group; without single‐ or dual‐task training; and continuing psychosocial treatment, including environmental adjustment). Results Overall, 262 participants were enrolled in the study between July 2020 and July 2021. Of these, 261 participants were included in the analysis (SDT‐001, n = 108; single‐task, n = 107; observation, n = 46). ADHD Rating Scale‐IV (ADHD‐RS‐IV) scores (physician's assessment) decreased gradually, with greater reduction in SDT‐001 versus the single‐task group at week 6 (ADHD‐RS‐IV‐Total score, least‐squares mean change from baseline [95% confidence interval] −7.5 [9.0, −6.1] vs. −6.5 [−7.9, −5.0], P = 0.2112). Reductions in inattention and hyperactivity/impulsivity scores were maintained during 4‐week follow‐up after treatment completion. At week 6, the scores of both groups improved compared to the nonrandomized observation group in post hoc analysis. Conclusion These findings suggest SDT‐001 as a promising treatment option, addressing the challenges of psychosocial treatment and pharmacotherapy in Japanese children and adolescents with ADHD.